Answer: 634.653
I don't know if this is right or not, but i hope this helps
Answer: ![\frac{11tc+5g}{66t}=n](https://tex.z-dn.net/?f=%5Cfrac%7B11tc%2B5g%7D%7B66t%7D%3Dn)
Step-by-step explanation:
You have the equation
.
Then, to solve for the variable
from the equation you need:
Make the subtraction of the right side of the equation:
(As the denominators are 1 and
, the least common denominator is
)
![c=\frac{(6n)(11t)-5g}{11t}\\\\c=\frac{66nt-5g}{11t}](https://tex.z-dn.net/?f=c%3D%5Cfrac%7B%286n%29%2811t%29-5g%7D%7B11t%7D%5C%5C%5C%5Cc%3D%5Cfrac%7B66nt-5g%7D%7B11t%7D)
Multiply
to both sides:
![(11t)c=(\frac{66nt-5g}{11t})(11t)\\\\11tc=66nt-5g](https://tex.z-dn.net/?f=%2811t%29c%3D%28%5Cfrac%7B66nt-5g%7D%7B11t%7D%29%2811t%29%5C%5C%5C%5C11tc%3D66nt-5g)
Add
to both sides:
![11tc+5g=66nt-5g+5g\\\\11tc+5g=66nt](https://tex.z-dn.net/?f=11tc%2B5g%3D66nt-5g%2B5g%5C%5C%5C%5C11tc%2B5g%3D66nt)
And finally divide both sides by
:
![\frac{11tc+5g}{66t}=\frac{66nt}{66t}\\\\\frac{11tc+5g}{66t}=n](https://tex.z-dn.net/?f=%5Cfrac%7B11tc%2B5g%7D%7B66t%7D%3D%5Cfrac%7B66nt%7D%7B66t%7D%5C%5C%5C%5C%5Cfrac%7B11tc%2B5g%7D%7B66t%7D%3Dn)
Answer:
f(-1)=6×(-1)^-4=6/(-1)^4=6/1=6